An Analysis Repair On Utterances In The Conversation Of The Magic Of Belle Isle Movie Manuscript - Hidayah, Nur; , Dra. Malikatul Laila, M. Hum; , Dr. Dwi Haryanti, M.Hum (2015)
The reseacrh paper analyzes repair on the conversation in The Magic of Belle Isle movie. The study aims at (1) identifying the types of repair in The Magic of Belle Isle movie and (2) describing the function of repair in The Magic of Belle Isle movie. The type of this research is descriptive qualitative research. The object of the study is repair analysis found on the conversation in the movie entitled The Magic of Belle Isle. The data of this reseacrh are the dialogues which contain repair in The Magic of Belle Isle movie manuscrpit. The data source of this research is the script The Magic of Belle Isle. The method used by the writer in collecting data are observation and documentation with step: watching, writing, noting, selecting and coding. In analyzing the data, the writer identifies the types of repair by Brian Paltridge and describes the function of repair by the pragmatic context. The results of the study show that all the types of repair, there are: self repair and other repair. There are some kinds of the function of the types of repair in repair analysis on the conversation; to ask, to clarified, to replaced, to suggest, to assert, to explain and to convince.